Plasma growth hormone profile in buffalo neonates - Jailkhani, Sujata; Madan, M L (The Indian Journal of Animal Sciences, 2012)
A sensitive radioimmunoassay (RIA) procedure for estimation of growth hormone in buffalo plasma using highly purified bovine GH was developed, Radioiodination of the hormone was carried out with carrier free 125N-I. Immune reaction was performed using buffalo plasma, buffer, labelled antigen and the antiserum at room temperature. Separation of antibody-bound GH from free GH was accomplished with goat antirabbit gamma globulin. The calibration curve was sensitive from 19.5 pg to 50 ng/ml. Using this procedure, mean plasma concentration of GH was found to be significantly high (P<0.05) on day 3 (31 .25Â±4.13 ng/ml) compared to days 10 and 30. The data are suggestive of high postnatal levels in buffalo calves during first month of life.